A tale of two cities - Dickens, Charles, 1812-1870 (Vintage classics, 2008)
Young Englishman Sidney Carton gives his life during the French Revolution to save the husband of the woman he loves, in an epic novel set against the turbulent backdrop of eighteenth-century France.